2015
DOI: 10.3892/or.2015.4439
|View full text |Cite
|
Sign up to set email alerts
|

β-lapachone suppresses the proliferation of human malignant melanoma cells by targeting specificity protein 1

Abstract: β-lapachone (β-lap), a novel natural quinone derived from the bark of the Pink trumpet tree (Tabebuia avellanedae) has been demonstrated to have anticancer activity. In this study, we investigated whether β-lap exhibits anti-proliferative effects on two human malignant melanoma (HMM) cell lines, G361 and SK-MEL-28. The effects of β-lap on the HMM cell lines were investigated using 3-(4,5-dimethylthiazol-2-yl)‑5-(3-carboxymethoxyphenyl)‑2-(4-sulfophenyl-2H-tetrazolium (MTS) assay, 4',6-diamidino-2-phenylindole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…It ranks as the fifth most common cancer for male and the seventh most common malignancy in female (2,3). In recent years, a large number of studies have focused on the pathogenesis of MM, and deregulation of oncogenes and tumor suppressors have been reported to play key roles in the development and progression of MM (4,5). However, the detailed molecular mechanism underlying MM still remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It ranks as the fifth most common cancer for male and the seventh most common malignancy in female (2,3). In recent years, a large number of studies have focused on the pathogenesis of MM, and deregulation of oncogenes and tumor suppressors have been reported to play key roles in the development and progression of MM (4,5). However, the detailed molecular mechanism underlying MM still remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The present study focused on β-lap, a natural quinone derived from the bark of the Lapacho tree (12,13). Previous studies have revealed that β-lap acts as a potent anti-proliferative agent, inhibiting topoisomerase I/II (26,32,33), specificity protein 1 (26) and the cell cycle (34). It has also been shown that repetitive oxidation-reduction of β-lap by NQO1 generates ROS in tumor cells (14), thus contributing to cytotoxicity in malignancies, including pancreatic cancer (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The viabilities of the remaining six cell lines were also tested and the IC 50 values are presented in Table I. These corresponded to the values that had been reported previously for SK-MEL-28 and another cell line, G361 (26). The association between the basal expression levels of NQO1 and the IC 50 values of β-lap in eight melanoma cell lines were then compared.…”
Section: Effect Of β-Lap On Melanoma Cell Linesmentioning
confidence: 99%
“…In addition to NFD, another quinone β-lapachone (β-LAP) has been documented to be present in trace amounts in the non-fractionated aqueous extracts of TA and TNM. This minor constituent, at higher pharmacological concentrations, exhibits anti-cancer activity in preclinical xeno-transplant models of epithelial organ site cancers via distinct molecular mechanisms (15,16,(39)(40)(41). However, it is important to recognize that at the low concentrations of TA or TNM used, the levels of β-LAP remain essentially undetectable (42).…”
Section: Discussionmentioning
confidence: 99%